2018
DOI: 10.1186/s12866-018-1235-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic properties and stx phage characterization of Escherichia coli O157 isolated from animal sources in a developing country setting

Abstract: BackgroundIn many Asian countries including Bangladesh E. coli O157 are prevalent in animal reservoirs and in the food chain, but the incidence of human infection due to E. coli O157 is rare. One of the reasons could be inability of the organism from animal origin to produce sufficient amount of Shiga toxin (Stx), which is the main virulence factor associated with the severe sequelae of infection. This study aimed to fill out this knowledge gap by investigating the toxigenic properties and characteristics of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Different studies have reported the detection of STEC by PCR or qPCR from different matrices [35][36][37][38] and the challenges of subsequently obtaining cultured STEC isolates. This significant discrepancy may be related to dead and injured cells, cells in a viable but non-culturable (VBNC) state, the presence of free DNA and free Stx bacteriophages in the samples [10,[39][40][41][42][43][44]. In addition, the microbial communities can have an important influence on the survival capabilities of STEC in environmental substrates and consequential cultural isolation [24,45].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported the detection of STEC by PCR or qPCR from different matrices [35][36][37][38] and the challenges of subsequently obtaining cultured STEC isolates. This significant discrepancy may be related to dead and injured cells, cells in a viable but non-culturable (VBNC) state, the presence of free DNA and free Stx bacteriophages in the samples [10,[39][40][41][42][43][44]. In addition, the microbial communities can have an important influence on the survival capabilities of STEC in environmental substrates and consequential cultural isolation [24,45].…”
Section: Discussionmentioning
confidence: 99%
“…This lysogen and another one obtained in a previous study (Krüger et al, ) showed similar levels of stx 2a expression, infective phages and extracellular Stx production, in comparison with the corresponding wild‐type strains. Likewise, Rahman, Nabi, Asadulghani, Faruque, and Islam () obtained the same high Stx titre both in a lysogen and its wild‐type strain when studied at basal conditions, and Muniesa, Blanco, et al () have reported a high spontaneous phage release and high inducibility after mitomycin C treatment in lysogens obtained with E. coli DH5α.…”
Section: Discussionmentioning
confidence: 71%
“…Rahman et al () attributed the low incidence of human infection with E. coli O157 in many Asian countries to the low frequency of strains that carry inducible phages and produce Stx2. Among O157 STEC isolates from food and food‐producing animals, they only found inducible Stx phages among those isolates that produced Stx2.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, q gene detection in those strains may be due to the presence of defective phages that lack stx genes. Regarding the q21 allele, none strain was found carrying this allele, which has been identified principally in STEC strains with low or null Stx production frequently isolated from beef, animal origin, and the environment in Asian countries, where these are widely distributed [32][33][34]10].…”
Section: Discussionmentioning
confidence: 99%